Species Composition and Toxigenic Potential of Fusarium Isolates Causing Fruit Rot of Sweet Pepper in China - Wang, Jianhua (Toxins (Basel), 2019)
Apart from causing serious yield losses, various kinds of mycotoxins may be accumulated in plant tissues infected by Fusarium strains. Fusarium mycotoxin contamination is one of the most important concerns in the food safety field nowadays. However, limited information on the causal agents, etiology, and mycotoxin production of this disease is available on pepper in China. This research was conducted to identify the Fusarium species causing pepper fruit rot and analyze their toxigenic potential in China. Forty-two Fusarium strains obtained from diseased pepper from six provinces were identified as F. equiseti (27 strains), F. solani (10 strains), F. fujikuroi (five strains). This is the first report of F. equiseti, F. solani and F. fujikuroi associated with pepper fruit rot in China, which revealed that the population structure of Fusarium species in this study was quite different from those surveyed in other countries, such as Canada and Belgium. The mycotoxin production capabilities were assessed using a well-established liquid chromatography mass spectrometry method. Out of the thirty-six target mycotoxins, fumonisins B(1) and B(2), fusaric acid, beauvericin, moniliformin, and nivalenol were detected in pepper tissues. Furthermore, some mycotoxins were found in non-colonized parts of sweet pepper fruit, implying migration from colonized to non-colonized parts of pepper tissues, which implied the risk of mycotoxin contamination in non-infected parts of food products.